Volume 2: Materials; Joint MSEC-NAMRC-Manufacturing USA 2018
DOI: 10.1115/msec2018-6318
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Friction Stir Welding of High Density Polyethylene

Abstract: Friction stir welding of high density polyethylene sheets was performed at different rotational and welding speeds and the material temperature close to the welding zone was monitored by infrared thermography and thermocouple measurements. Welding quality was evaluated by macrostructure analysis and tensile testing. Fracture surfaces of the tensile specimens were also analyzed. It was found that weld quality is highly dependent on the temperature of the material in the welding zone. For some specific welding c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Still, all welds presented residual depressions along the weld surfaces due to material shrinkage during cooling, a typical phenomenon on FSW of polymers. Similar observations were reported by Sheikh-Ahmad et al [ 22 ].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Still, all welds presented residual depressions along the weld surfaces due to material shrinkage during cooling, a typical phenomenon on FSW of polymers. Similar observations were reported by Sheikh-Ahmad et al [ 22 ].…”
Section: Resultssupporting
confidence: 92%
“…Due to the poor thermal conductivity and low melting temperature of polymers, previous studies demonstrated that, typically, the conventional FSW tool is not suitable for welding polymers. The heat generated by a rotating shoulder is concentrated on the surface of the polymer, promoting material burning and heavy material projection, commonly known as flash defect [ 21 , 22 ]. Consequently, the tensile strength of welds produced by conventional FSW is normally reduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation